Impact of frailty on postoperative complications in older adults after hip fracture: a systematic review of observational studies - Tian, Peng; Yang, Yi; He, Tianjiao; Wang, Liping; Zhang, Qiurong; Cai, Yingying (Frontiers in Medicine, 2025)
PurposeFrailty, a common syndrome involving multisystem impairment in older adults, is a significant preoperative concern for hip fracture patients. However, its specific link to postoperative complications remains unclear. This systematic review and meta-analysis investigates the association between preoperative frailty and adverse surgical outcomes in this geriatric population.MethodsWe comprehensively searched several databases, including China National Knowledge Infrastructure PubMed, Embase, Web of Science, (China National Knowledge Infrastructure, CNKI), Wanfang, VIP and the Cochrane Library from January 1, 2000, to September 2024. We focused on cohort studies that examine how frailty affects prognosis after hip fracture surgery in older adults. Two researchers independently screened literature, extracted data, and assessed the quality of included studies using the Newcastle-Ottawa Scale (NOS). We used Stata 15.0 to perform the meta-analyses.ResultsThis review included 27 cohort studies, consisting of 19 retrospective and 8 prospective studies, involving a total of 243,264 patients. When compared to non-frail patients, frailty statistically significantly increases the risk of postoperative mortality following hip fracture. Specifically, frailty is associated within-hospital mortality [(relative risk, RR) = 3.20, 95% (confidence interval, CI): 1.93, 5.31], 30-day mortality (RR = 3.91, 95%CI: 1.89, 8.07), and 1-year mortality (RR = 1.50, 95%CI: 1.39, 1.61). Frailty also increases the rate of complications (RR = 2.81, 95%CI: 1.67, 4.74), postoperative delirium (RR = 4.44, 95%CI: 2.34, 8.41), pneumonia (RR = 4.09, 95%CI: 2.39, 7.01), and 30-day readmission (RR = 1.75, 95%CI: 1.56, 1.96).ConclusionFrailty increases both short-term and long-term mortality following hip fracture surgery in older patients. Additionally, frailty is associated with a higher overall rate of complications, including the 30-day readmission.